PENGARUH KEPEMIMPINAN DIGITAL PADA KEUNGGULAN BERSAING GENERASI Z JAWA TENGAH - Zuhrufillah, Irfani; Putri, Puspita Lianti (Applied Research in Management and Business, 2024)
Digital Leadership which able to accommodate current digital activities, is one of the variables that can build competitive advantage. The aims of this research is to test the influence of digital leadership in competitive advantage on generation Z. The hypothesis testing method uses simple linear regression because it only has one independent variable, Digital Leadership, which is then tested on the dependent variable, Competitive Advantage. The results obtained show that Digital Leadership has a significant positive influence on Competitive Advantage. In future research, the author suggests that testing needs to add other independent variables, such as innovative work behavior.